2021
DOI: 10.1590/1806-9282.20210610
|View full text |Cite
|
Sign up to set email alerts
|

Can blood urea Nitrogen-to-Albumin ratio predict mortality in patients with moderate-to-severe COVID-19 pneumonia hospitalized in the intensive care unit?

Abstract: OBJECTIVE: Many laboratory parameters allow to follow up the course of the disease and reveal its clinical severity, particularly in patients with coronavirus disease 2019 (COVID-19) pneumonia. In this study, we aimed to investigate the role of the blood urea nitrogen-to-albumin ratio in predicting the mortality in COVID-19 patients with moderate-to-severe disease who are hospitalized in the intensive care unit.METHODS: A total of 358 patients who were hospitalized in intensive care unit at our hospital betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
(25 reference statements)
1
13
0
1
Order By: Relevance
“…Albumin based inflammatory parameters (UAR, LAR, CAR, DAR, FAR and PAR) were also studied in critical illnesses as well as COVID-19 and they were all found to be useful in the prediction of prognosis. 20 26 Consistent with these studies, we also found that albumin based inflammatory parameters were significantly higher in mortal cases compared with survived ones.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Albumin based inflammatory parameters (UAR, LAR, CAR, DAR, FAR and PAR) were also studied in critical illnesses as well as COVID-19 and they were all found to be useful in the prediction of prognosis. 20 26 Consistent with these studies, we also found that albumin based inflammatory parameters were significantly higher in mortal cases compared with survived ones.…”
Section: Discussionsupporting
confidence: 89%
“…5 Apart from NLR, many other inflammatory parameters showing systemic inflammation were found to be useful in predicting mortality in COVID-19 patients. [19][20][21][22][23][24][25][26][27][28][29] The common mechanism of the effect of these parameters to the disease mortality is that systemic inflammation has a crucial role in the pathogenesis and mortality of COVID-19. 6,8 Hemogram based inflammatory parameters were previously investigated in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…3). [20][21][22][23][31][32][33] Sensitivity analysis reinforced the robustness of the result by showing no significant impact of the finding from a single study on the overall outcome. Publication bias was not investigated because only 7 studies were available.…”
Section: Discussionmentioning
confidence: 97%
“…5). [20][21][22][23]31,33] Linear regression analysis of sROC generated from mathematical computation of true and false positivity (1-specificity) of each study showed an AUC of 0.81 (95% CI = 0.77-0.84) (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation